(untitled) (BIRDEM Medical Journal, 2016)
Background: A large number of neonates in intensive care unit require mechanical ventilation due to various disease conditions. There has been a dramatic fall in neonatal mortality in developed countries with the advent of mechanical ventilation and the concept of neonatal intensive care. But still fatality rate is very high in developing countries. So, this study or was done to identify the immediate hospital outcome of the neonates who required mechanical ventilation. Methods: This study was done in Special Care Baby Unit, BIRDEM General Hospital from July 2009 to June 2010. All neonates requiring mechanical ventilation during the study period were prospectively enrolled in this study. During the time of mechanical ventilation neonates were followed up to observe any complication till discharge or death. Results: Total 37 neonates were enrolled in the study. Among them 27 (73%) were preterm and 30 (81%) were low birth weight. Respiratory distress syndrome was the most common reason for ventilation accounting for 17 (45.9%) cases. The other indications were perinatal asphyxia (9, 24.3%), congenital pneumonia (5, 13.5%), septicemia (5, 13.5%) and meconium aspiration syndrome (1, 2.7%). The most common complication during the period of ventilation was septicemia (14, 37.8%). Other complication included pneumothorax (6, 16.2%), acute renal failure (5, 13.3%), pneumonia (5, 13.3%), pulmonary hemorrhage (3, 8.1%), intraventricular hemorrhage (2, 5.4%) and heart failure (2, 5.4%). The fatality rate was 38% and most of the infant died of perinatal asphyxia (5, 35.7%), septicemia (4, 28.5%), respiratory distress syndrome (3, 21.5%) and congenital pneumonia (2, 14.3%). Conclusion: Respiratory distress syndrome was the most common reason for mechanical ventilation followed by perinatal asphyxia and septicemia. Most common complication during mechanical ventilation was septicemia which was also a common cause of death. Another important cause of death was perinatal asphyxia Birdem Med J 2016; 6(1): 22-25